The ethics and law of safeguarding. (2nd November 2022) - Ellis, Hannah; Ellis, Emily; Ellis, Peter
Abstract : Hannah Ellis, Emily Ellis and Peter Ellis discuss safeguarding and the law in relation to kidney care and how it is applied to main patient safety